Pendidikan di Revolusi Industri 4.0: Studi Kasus Evaluasi Kurikulum Merdeka di Indonesia: Education in the Industrial Revolution 4.0: A Case Study of Independent Curriculum Evaluation in Indonesia - Yanti, Dawi; Prastawa, Singgih; Utomo, Widodo Febri; Wiliyanti, Vandan; Utomo, Bekti (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The Industrial Revolution 4.0 has driven significant changes in the education system, including in Indonesia, with the introduction of the Independent Curriculum. The Industrial Revolution 4.0 has brought significant changes to various aspects of life, including the education sector. This era is marked by the integration of digital, physical, and biological technologies that change the way humans live, work, and learn. Education, as the foundation for human resource development, must adapt to these changes to prepare the younger generation to face future challenges and opportunities. The method used is a literature study analysis of various previous studies and case studies. The results of the study show that the Independent Curriculum has the potential to improve 21st century skills, such as critical thinking, creativity, collaboration, and digital literacy. However, significant challenges in its implementation include lack of teacher understanding, limited infrastructure, and differences in readiness between regions. The Independent Curriculum shows potential in improving student competencies, especially in terms of critical thinking skills, creativity, collaboration, and digital literacy. The implementation of the Independent Curriculum at various levels of education faces a number of challenges. This study reveals that the Independent Curriculum has the potential to bring positive changes to the Indonesian education system by improving student competencies in accordance with the demands of the Industrial Revolution 4.0. Technology support, teacher training, and community involvement have proven to be important for successful implementation. Recommendations include the development of contextual learning modules, increased technology support, and holistic assessment. These findings provide insights for the development of better education policies in the digital era.